PENERAPAN MODEL PEMBELAJARAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 023 SUNGAI SEGAJAH KECAMATAN KUBU - Ulfa Yani Ulfa Yani; Zariul Antosa Zariul Antosa; Lazim N Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study was conductedbecause of the low IPS student learningoutcomes, with an average grade of 62.4. While the value of minimumcompleteness criteria (KKM) IPS 65. This research is a classroom actionresearch (CAR). Aiming to improve learning outcomes IPS 023 fourth gradestudents of SDN Segajah River Kubu district of Rokan Hilir. Formulation of theproblem: Is the application of the concept map learning model to improvelearning outcomes IPS 023 fourth grade students of SDN Segajah River Kubudistrict of Rokan Hilir. Student learning outcomes before held PTK with anaverage of 62.4 with less category. Meanwhile, after the action research in thefirst cycle with an average of 75 with enough categories and the second cycle withan average of 84.75 with very good category. From this data it can be seencomparison of improving student learning outcomes from a base score of 12.6while kesiklus one of two kesiklus base score of 22.35. While the average teacheractivity in the first cycle reaches 62.5%, while in the second cycle and reaches81.25% of students in the first cycle normaly reach 64.58% and in the secondcycle reaches 79.16%. These results prove that the application of the concept maplearning model to improve learning outcomes IPS 023 fourth grade students ofSDN Segajah River Kubu district Rokan Hilir.Keywords: Model learning concept maps, IPS Learning Outcomes